Epidemiology of Cardiovascular Diseases Risk Factors and Hypertension in a Community-Based Suburban Population in Nepal - Karmacharya, Biraj Man (My University, 2015)
Background: The epidemiology of cardiovascular diseases (CVD) risk factors and the CVD risk profile, in the Nepalese population is not fully understood. Almost a third of the adult Nepalese population is estimated to be hypertensive, but there is still lack of information on the associations of socio-demographic characteristics and other CVD risk factors with hypertension. The level of knowledge, awareness, treatment and control of hypertension, and their associated factors is also poorly understood. Objectives: This dissertation aimed to determine the prevalence of CVD risk factors including smoking, hypertension, low physical activity, low consumption of fruits and vegetables, diabetes, high total cholesterol and triglycerides, low HDL; describe CVD risk profiles and their relationship with socio-demographic factors; investigate the association of prevalent hypertension with socio-demographic characteristics and CVD risk factors; and assess knowledge, awareness, treatment and control of hypertension, in a random sample of adults residing in Dhulikhel, Nepal. Methods: In this cross-sectional study, we enrolled 1073 participants (18 years and older) from a random selection of one third of households in the town of Dhulikhel in central Nepal. Prevalence of CVD risk factors was ascertained using standard case definitions and cut-offs. We measured the adverse CVD risk profiles of the participants by summing the presence of the following conventional modifiable CVD risk factors: current smoker, overweight or obese, less than recommended physical activity, less than recommended consumption of fruits and vegetables and hypertension. Hypertension was defined as a systolic blood pressure 140 mm Hg or greater, or diastolic blood pressure 90 mm Hg or greater, or receiving antihypertensive medication. Hypertension knowledge was categorized dichotomously as being able to mention at least one risk factor of hypertension or not being able to mention any risk factors of hypertension. Among hypertensive patients we assessed awareness (self-report that a doctor or other health worker had told the participant they had hypertension), treatment (self-report of being on medications for hypertension management) and control (SBP<140mm Hg and DBP<90mm Hg). The prevalence estimates of CVD risk factors were standardized to the age of the Nepalese population reported in the 2011 census. Multinomial multivariate logistic regression with Generalized Estimating Equation (GEE) was used to estimate the adjusted associations, of different socio-demographic characteristics with adverse CVD risk profiles. Multivariate logistic regression utilizing GEE was used to investigate the associations of socio-demographic characteristics and other CVD risk factors with hypertension prevalence, knowledge, awareness, treatment and control. Results: Among the 1073 participants, 41.6% were males and 58.4% were females. The mean age of the participants was 40.3 years (SD: 16.3). Age standardized prevalence showed that more than a third of the participants were obese or overweight in both sexes (31.7% in males and 37.2% in females). Both former and current smoking rates were nearly double among males compared to females [current (27.7% versus 13.4%) and former (11.1% versus 5.6%)]. Nearly half of the participants had less than 5 servings of fruits and vegetables per day in both sexes. Thirty seven percent males and 41.4% females had less than the recommended level of physical activity. Hypertension was twice as common in males (37.3%) compared to females (17.3%). Among 479 participants, who had their blood samples collected for biochemical investigations, almost a third were found to be diabetic (35.5% in males and 25.5% in females). Men had twice as high a prevalence of high total cholesterol (5.7%) and high triglyceride (13.3) compared to women (2.9% and 5.3% respectively). Only 10.0% males and 13.7% females had no conventional modifiable CVD risk factors. Males had significantly higher adverse CVD risk profiles compared to females (p=0.024). In the multinomial multivariate model, age was significantly associated with an adverse risk profile in both sexes (p<0.001). In terms of ethnicity, Newars had significantly higher risk of having three or more CVD risk factors compared to Brahmins (OR: 4.54, 95% CI: 2.03-10.1; p<0.001). Those in the highest income quartile had significantly lower risk of having three or more CVD risk factors compared to those in the lowest quartile (OR: 0.50, 95% CI: 0.26-0.97;p=0.042). In the multivariate model, males had significantly higher risk of hypertension (OR: 2.52, 95% CI: 1.69-3.75, p=<0.001) compared to females. Age was also significantly associated with hypertension prevalence (p<0.001). The Newar ethnic group had 5.65 times higher risk of hypertension (95% CI: 3.12-10.21, p<0.001) compared to Brahmins. Being overweight or obese were associated with an increased risk of 2.61 (95% CI: 1.81-3.77, p<0.001) and 6.74 (95% CI: 3.75-12.11, p<0.001) times respectively. A total of 43.1% of the participants were not able to mention a single risk factor for hypertension. In the multivariate model, males were almost twice as likely to have knowledge of hypertension compared to females (OR: 2.04; 95% CI: 1.22-3.40, p=0.006). Among different ethnic groups, Newars were most likely to have knowledge of hypertension (OR: 2.13; 95% CI: 1.26-3.57, p<0.001) when compared to Brahmins. Compared to those with no formal education, those with up to high school and those with more than high school education were 2.89 times (95% CI: 1.85-4.50, <0.001) and 9.37 times (95% CI: 4.40-19.95, p<0.001) more likely to cite at least one risk factor of hypertension, respectively. A total of 43.6% of the hypertensive participants were aware that they had high blood pressure. In multivariate model, only ethnicity appeared to be associated with awareness. A total of 76.1% of those who were aware of their hypertension status were currently on treatment. Only 35.3% of those on treatment had good blood pressure control. Conclusions: Overall, the findings reported here suggest that the burden of CVD risk factors in Nepal might be greater than previously estimated. The CVD risk profile in this population was also very concerning. Newar ethnicity appears to be independently associated with hypertension compared to Brahmins. The levels of knowledge, awareness, treatment and control of hypertension were very low. The lack of knowledge of hypertension was associated with women gender, Brahmin ethnicity and no formal education. We did not find significant associations of hypertension awareness with socio-demographic or other CVD risk factors.
Thesis (Ph.D.)--University of Washington, 2015
Keywords: Cardiovascular; Epidemiology; Hypertension; Nepal; Risk Factors; Epidemiology; epidemiology